Prognos av vägars bärförmåga vid tjällossningen : Användning av "Minnesotamodellen" på en teststräcka i Sverige - Berglund, Andreas (Luleå tekniska universitet, Geoteknologi, 2010)
The global trend towards a warmer climate and temperatures near or just above 0 °C during winter months, will most likely be more common in future. One of the consequences of this climate change could, in a worst-case scenario, be freezing and thawing over a significant part of the winter with corresponding road bearing capacity problems. Bearing capacity problems may lead to increased costs to society when heavy traffic is forced to change route or carry less weight. In addition, road maintenance costs will increase. According to pulp industry calculations, this industry sector will face additional costs in the range of 510-590 Million SEK every year due to road bearing capacity problems. In addition to this, the costs related to the rapidly growing bio fuel industry will be added. If a reliable forecast of load-bearing capacity problems and potential load restrictions on roads can be found, it would be cost effective for road administration and society. This research report is a part of a work to find methods to forecast bearing capacity problems on roads. The report gives an idea of the possibility to use the temperature based model used in Minnesota, USA in Sweden. The evaluation is done by comparing falling weight deflectometer (FWD) test results with the results from the temperature based forecast model. Temperatures and FWD data were collected in 1997 on a road approximately 7 km outside Luleå, Sweden. The road structure was from the surface: 0,10 m asphalt, 0,40 m sandy gravel/gravely clayey sand and 3,0 m silty clay overlaying a silty moraine. In the report the FWD concept, as well as the FWD parameters of importance are described. How the temperature data was collected is described. The temperatures were collected at a depth of 0,20 m and 0,12 m below the asphalt layer respectively. FWD data was normalised to a force of 50kN. The radius of the segmented falling plate was 0,12 m and all calculations were carried out in accordance with Swedish guidelines. Based upon the FWD tests, the following ...